Effect of spectral cross-correlation on multiaxial fatigue damage: simulations using the critical plane approach (Fracture and Structural Integrity, 2017)
The present paper aims to discuss a frequency-domain multiaxial fatigue criterion based on the critical plane approach, suitable for fatigue life estimations in the presence of proportional and non-proportional random loading. The criterion consists of the following three steps: definition of the critical plane, Power Spectral Density (PSD) evaluation of an equivalent normal stress, and estimation of fatigue damage. Such a frequency-domain criterion has recently been validated by using experimental data available in the literature, related to combined proportional and non-proportional bending and torsion random loading. The comparison with such experimental data has been quite satisfactory. In order to further validate the above criterion, numerical simulations are herein performed by employing a wide group of combined bending and torsion signals. Each of such signals is described by an ergodic, stationary and Gaussian stochastic process, with zero mean value. The spectrum of each signal is assumed to be represented by a PSD function with rectangular shape. Different values of correlation degree, variance and spectral content are examined.
Keywords: Critical plane-based criterion; Frequency-domain criterion; Power Spectral Density